A STRIDE BASED APPROACH TO FORTIFY DIGITAL HEALTHCARE SECURITY - Summia Aziz,; Dr. Shariq Hussain, (Spectrum of Engineering Sciences, 2025)
The study underscores the paramount significance of robust threat identification in Smart Health Systems (SHS) to enhance reliability and practicality. This study employs a methodology that effectively utilizes the Microsoft Threat Modelling Tool, leveraging the STRIDE framework, to comprehensively identify threats within the SHS. Through the incorporation of the DREAD model, this approach facilitates efficient risk management, prioritizing threats based on Damage, Reproducibility, Exploitability, Affected Users, and Discoverability. The systematic framework proposed in this research proves instrumental in identifying threats at early stages, streamlining the mitigation process, and contributing to the overall security resilience of Smart Health Systems. This work aims to fortify the foundation of SHS by addressing security challenges proactively, ensuring a reliable and secure digital healthcare ecosystem.